Corporate Self-Regulation vs. Ex-Ante Regulation of Network Access: A Model of the German Gas Sector - Georg Meran; Christian R. von Hirschhausen (Deutsches Institut für Wirtschaftsforschung (DIW), 2004)
This paper compares the outcomes of corporate self-regulation and traditional ex-ante regulation of network access to monopolistic bottlenecks. In the model of self-regulation, the domestic gas supplier and network owner and the monopsonistic gas customer fix quantities and the network access price, whereas the competitive fringe of foreign gas producers (third party) and the household customers are excluded from the agreement. The results are then compared with the outcome of traditional ex-ante regulation. We find that while industrial self-regulation leads to an exploitation of households, the effect on the foreign producers is unclear.
Keywords: L95; D43; L13; L51; 330